2021
DOI: 10.3390/ijerph18084296
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Environment Associates with Trimethylamine-N-Oxide (TMAO) as a Cardiovascular Risk Marker

Abstract: Background: Neighborhoods and the microbiome are linked to cardiovascular disease (CVD), yet investigations to identify microbiome-related factors at neighborhood levels have not been widely investigated. We sought to explore relationships between neighborhood deprivation index (NDI) and the microbial metabolite, trimethylamine-N-oxide. We hypothesized that inflammatory markers and dietary intake would be mediators of the relationship. Methods: African-American adults at risk for CVD living in the Washington, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“… 142 In a recent study from our lab, we demonstrated that within a cohort of Black individuals, neighborhood deprivation index as a marker of neighborhood-level SES was associated with increased levels of TNF-α and IL-1β. 143 We also determined that neighborhood deprivation was associated with trimethylamine N-oxide, 143 a biomarker associated with the gut microbiome, cardiovascular risk factors, and CVD mortality. 144 Interestingly, our data showed that the neighborhood deprivation index-to-trimethylamine N-oxide relationship was significantly mediated by the TNF-α and IL-1β response, 143 suggesting a need for future work to examine how inflammation induced by adverse SDoH may relate to the gut microbiome and CVD risk.…”
Section: Social Determinants Of Health and The Biology Of Adversitymentioning
confidence: 99%
See 1 more Smart Citation
“… 142 In a recent study from our lab, we demonstrated that within a cohort of Black individuals, neighborhood deprivation index as a marker of neighborhood-level SES was associated with increased levels of TNF-α and IL-1β. 143 We also determined that neighborhood deprivation was associated with trimethylamine N-oxide, 143 a biomarker associated with the gut microbiome, cardiovascular risk factors, and CVD mortality. 144 Interestingly, our data showed that the neighborhood deprivation index-to-trimethylamine N-oxide relationship was significantly mediated by the TNF-α and IL-1β response, 143 suggesting a need for future work to examine how inflammation induced by adverse SDoH may relate to the gut microbiome and CVD risk.…”
Section: Social Determinants Of Health and The Biology Of Adversitymentioning
confidence: 99%
“… 143 We also determined that neighborhood deprivation was associated with trimethylamine N-oxide, 143 a biomarker associated with the gut microbiome, cardiovascular risk factors, and CVD mortality. 144 Interestingly, our data showed that the neighborhood deprivation index-to-trimethylamine N-oxide relationship was significantly mediated by the TNF-α and IL-1β response, 143 suggesting a need for future work to examine how inflammation induced by adverse SDoH may relate to the gut microbiome and CVD risk. Ultimately, more work is needed to link neighborhood factors to inflammatory markers and immune cell function.…”
Section: Social Determinants Of Health and The Biology Of Adversitymentioning
confidence: 99%
“…The increased concentration of TMAO in the body has been associated with health problems such as inflammatory processes, risk of arteriosclerosis, neurological disorders, or kidney damage, among other diseases. However, the mechanism associated with these damages is still unknown (Barrea et al, 2018 ; Brial et al, 2018 ; Chhibber-Goel et al, 2017 ; Coras et al, 2019 ; Dove et al, 2012 ; Farmer et al, 2021 ; Gatarek & Kaluzna-Czaplinska, 2021 ; Janeiro et al, 2018 ; Koeth et al, 2013 ). One of the characteristics of COVID-19 is the appearance of inflammatory processes, which could be leading to increased levels of TMAO in the urine of COVID-19 patients, as occurs with other inflammatory processes (Tang et al, 2015 ; Yang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nazmi et al also reported that higher levels of safety are associated with decreased IL-6 levels even after adjustment for race, ethnicity, and SES [ 146 ]. In a recent study from our own laboratory, we demonstrated that within a cohort of African Americans, neighborhood socioeconomic deprivation as measured by a neighborhood deprivation index (NDI) was associated with increased levels of TNFα and IL-1β [ 147 ]. We also determined that neighborhood deprivation was positively associated with TMAO [ 147 ], a biomarker associated with the microbiome, CV risk factors, and CVD mortality [ 148 , 149 ].…”
Section: Biomarkers Of Stress and The Biology Of Adversitymentioning
confidence: 99%
“…In a recent study from our own laboratory, we demonstrated that within a cohort of African Americans, neighborhood socioeconomic deprivation as measured by a neighborhood deprivation index (NDI) was associated with increased levels of TNFα and IL-1β [ 147 ]. We also determined that neighborhood deprivation was positively associated with TMAO [ 147 ], a biomarker associated with the microbiome, CV risk factors, and CVD mortality [ 148 , 149 ]. Interestingly, our data show that the NDI-to-TMAO relationship was significantly mediated by the TNFα and IL-1β [ 147 ], indicating the overall significant role of systemic low-grade inflammation in potentially accelerating CVD through multiple mechanisms, including effects related to the microbiome [ 150 ].…”
Section: Biomarkers Of Stress and The Biology Of Adversitymentioning
confidence: 99%